2011
DOI: 10.1038/onc.2011.418
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of mesenchymal stem cells by the synovial sarcoma-associated oncogene SYT–SSX2

Abstract: Cell identity is determined by its gene expression programs. The ability of a cell to change its identity and produce cell types outside its lineage is achieved by the activity of transcription controllers capable of reprogramming differentiation gene networks. The synovial sarcoma (SS)-associated protein, SYT–SSX2, reprograms myogenic progenitors and human bone marrow-derived mesenchymal stem cells (BMMSCs) by dictating their commitment to a pro-neural lineage. It fulfills this function by directly targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 42 publications
2
63
0
Order By: Relevance
“…Subsequent immunohistochemical and ultrastructural studies do not support a synovial origin of this tumor, and hence, the name is often considered a misnomer [8,9]. Synovial sarcoma is currently classified as a miscellaneous tumor of uncertain cellular origin, most likely to be derived from primitive mesenchymal cells that undergo differentiation [10][11][12]. This is supported by tumors that occur in organs devoid of synovial tissues, including the lung [13], heart [14], kidney [15], digestive tract [16], and bone marrow [17].…”
Section: Clinical Features Of a Historically Based Misnomermentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequent immunohistochemical and ultrastructural studies do not support a synovial origin of this tumor, and hence, the name is often considered a misnomer [8,9]. Synovial sarcoma is currently classified as a miscellaneous tumor of uncertain cellular origin, most likely to be derived from primitive mesenchymal cells that undergo differentiation [10][11][12]. This is supported by tumors that occur in organs devoid of synovial tissues, including the lung [13], heart [14], kidney [15], digestive tract [16], and bone marrow [17].…”
Section: Clinical Features Of a Historically Based Misnomermentioning
confidence: 95%
“…Deregulation of expression programs by SS18-SSX results in a series of biological events implicated in synovial sarcoma pathogenesis that likely include reprogramming of stem cell differentiation [10]. SS18-SSX activates oncogenic pathways such as IGF2 [66], Wnt [67][68][69], FGF [10,70], and [71], as well as reactivation of the anti-apoptotic pathway and the BCL2 oncogene [72,73].…”
Section: Translocation T(x;18)-critical Role In Oncogenic Transformationmentioning
confidence: 99%
“…. Several studies have showed that synovial sarcoma cells express mRNA transcripts of pluripotency factors such as Sox2 , Oct3/4 , and Nanog [45] and show stem-cell-like gene expression profiles [46], and that tumor cells lacking the BAF47 tumor suppressor subunit express stem-cell-like signatures [47]. Kadoch and Crabtree [48] demonstrated that SS18-SSX fusion protein binds to SWI/SNF-like BAF (chromatin-remodeling) complexes and evicts both the wild-type SS18 and the tumor suppressor BAF47.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of expression programs by SS18-SSX1/2 results in a series of biological events implicated in synovial sarcoma pathogenesis. These events likely include reprogramming of stem cell differentiation (Garcia et al, 2012), and untimely activation of oncogenic pathways such as IGF2 (Sun et al, 2006), Wnt (Horvai et al, 2006;Pretto et al, 2006;Bozzi et al, 2008), FGF (Ishibe et al, 2005;Garcia et al, 2012), and ephrin (Barco et al, 2007), as well as reactivation of the anti-apoptotic pathway and the bcl-2 oncogene (Mancuso et al, 2000, Jones et al, 2013.SS18-SSX2 variants are rare. One was described by Fligman et al (1995).…”
Section: Synovial Sarcomamentioning
confidence: 99%